Additive electrospraying: a route to process electrospun scaffolds for controlled molecular release†‡. (7th July 2015) - Guarino, Vincenzo; Altobelli, Rosaria; Cirillo, Valentina; Cummaro, Annunziata; Ambrosio, Luigi
Abstract : Electrohydrodynamics—i.e. electrospinning, electrospraying and atomization—are gaining a growing interest in drug delivery applications, because of a large number of advantages including improved therapeutic index, localized delivery/targeting and controlled drugs toxicity level. In the past, microstructured platforms fabricated by the assembly of electrospun fibers have demonstrated to exhibit interesting features as bioactive carriers including extended surface area and high molecular permeability because of fully interconnected pore architecture, thus making the opportunity to incorporate a wide range of actives/drugs for different use. In these systems, molecular release occurs via various molecular transport pathways namely diffusion, desorption and scaffold degradation which may be tuned through a careful control of fiber morphology and composition. However, several shortcomings still concern the possibility to incorporate bioactive species, not exposing molecules to fast and/or uncontrolled denaturation, thus preserving biochemical and biological fiber functionalities. In this context, additive electro spraying (AES)—i.e. integration of electrosprayed nanoparticles into electrospun fiber network—is emerging as interesting route to control "separately" release and functional properties of the scaffolds in order to support cell activities by independent cues, during the tissue formation. Here, we describe the current advances on the use of electrospraying and/or electrospinning until more innovative integrated AES approaches to design molecularly loaded platforms able to spatially and timely release active molecules for different use in tissue engineering and molecular targeting. Copyright © 2015 John Wiley & Sons, Ltd.